African Patrimonialism in Historical Perspective: Assessing Decentralized and Privatized Tax Administration - Kiser, Edgar; Sacks, Audrey (2012)
One of the most important political legacies of colonialism in Africa has been the reliance on the model of centralized bureaucratic administration, which has had disastrous consequences for African state-building. Like the colonial systems before them, these centralized bureaucracies have not functioned effectively. One of the main problems is a loose coupling between the formal bureaucratic structure of these states and the informal patrimonial elements, mainly patronage, that came to permeate them. Many scholars thus referred to these states as neopatrimonial. Over the past two to three decades, many governments have begun to replace centralized bureaucracies with different forms of partially patrimonial systems, including various forms of decentralization and partial privatization. This article uses both Weber and contemporary agency theory to evaluate the success of these new forms of partially patrimonial administration and to suggest ways in which they could be made more effective.